Vascular Endothelial Growth Factor Expression in Pulp Regeneration Treated By Hyaluronic Acid Gel in Rabbits - Rusul J. Hadi; Nawar Bahjet Kamil; Nada M. H. AL-Ghaban; Ban A Ghani; Alaa W. Izzat (College of Pharmacy University of Baghdad, 2024)
Among the most common dental problems, dental caries and trauma lead to the development of cavities and even tooth loss. Therefore, new regeneration techniques that are effective and toxic-free are needed. The use of scaffolds has created possibilities for the regeneration of tooth structure. Hydrogels made of hyaluronic acid have drawn many attention in regenerative medicine. Consequently, the objectives of the study were to estimate the impact of hyaluronic acid on pulp regeneration using histological evaluation and immunohistochemical localization of vascular endothelial growth factor (VEGF). The entire sample consisted of 20 teeth (right and left upper central incisors) from ten rabbits, Their ages were between 10 and 12 months. They were used for pulp exposure and coronal pulp tissue removal. After pulp exposure, hyaluronic acid hydrogels were injected into the pulp chambers of the right upper central incisors in the  experimental group to promote pulp regeneration. The pulp chambers of the left  upper central incisors considered as the control group, and they were temporarily filled in without the injection of hyaluronic acid. The histological and immunohistochemical evaluations were done in two time periods: the first and second week after pulp exposure. The histological results showed the formation of reparative dentin in the experimental group with a high mean value (56.3) regarding predentin thickness, especially in the second-week duration, and a significant difference as compared with the control group. The immunohistochemical results disclosed that the experimental group showed strong positive expression for vascular endothelial growth factor in different pulpal cells with the highest mean value of the number of positively expressed cells (34.3) in the second- week duration, with a significant difference as compared with the control group. Hyaluronic acid hydrogel had a supporting function in pulp regeneration, according to the findings of the current study. This was demonstrated by an increase in the expression of VEGF throughout the cells in pulp tissue.